2016
DOI: 10.1016/j.jpaa.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

On parameterized differential Galois extensions

Abstract: Abstract. We prove some existence results on parameterized strongly normal extensions for logarithmic equations. We generalize a result in [Wibmer, Existence of ∂-parameterized Picard-Vessiot extensions over fields with algebraically closed constants, J. Algebra, 361, 2012]. We also consider an extension of the results in [Kamensky and Pillay, Interpretations and differential Galois extensions, Preprint 2014] from the ODE case to the parameterized PDE case. More precisely, we show that if D and ∆ are two disti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Let K be a ∆ = {∂, δ}-field and k = K ∂ . We assume for simplicity that (k, δ) is a differentially closed field (this assumption was relaxed in [13,33,28]).…”
Section: Differential Modules and Their Galois Groupsmentioning
confidence: 99%
“…Let K be a ∆ = {∂, δ}-field and k = K ∂ . We assume for simplicity that (k, δ) is a differentially closed field (this assumption was relaxed in [13,33,28]).…”
Section: Differential Modules and Their Galois Groupsmentioning
confidence: 99%
“…This is not usual for the fields of functions that appear in the realm of algebraic geometry or complex analysis. It has been shown that, under some assumptions, this condition can be weakened by algebraic means as it is shown in [9,20,27].…”
Section: Introductionmentioning
confidence: 99%